Investigation of non-fatal occupational accidents and their causes in Turkish shipyards - GÖKYAY, ORHAN (My University, 2023)
This study reports new data for 1028 non-fatal occupational accidents dated between January 2010and April 2015 by applying the analytical hierarchy process (AHP) technique. A comprehensive surveywas conducted at four shipyards in Tuzla, Istanbul and Yalova regions in Turkey and a workplacequestionnaire appropriate for the AHP technique was carried out. The obtained results indicated thatinadequate safety equipment and protective clothing, unsuitable usage of machines and tools, and disobeyingoccupational health and safety (OHS) procedures were the most common risk factors for theaccidents. Hence the preventive measures could be identified by analyzing non-fatal accident data.After the identification of the descriptive measures, the priority order of these measures was asked ofthe occupational safety professionals in the shipbuilding industry, and we used the AHP method toevaluate the results.
Keywords: Çevre Mühendisliği; Çevre Bilimleri; Mühendislik ve Teknoloji; Environmental Engineering; Environmental Sciences; Engineering and Technology; Tarım ve Çevre Bilimleri (AGE); Mühendislik, Bilişim ve Teknoloji (ENG); Çevre / Ekoloji; ÇEVRE BİLİMLERİ; Agriculture & Environment Sciences (AGE); Engineering, Computing & Technology (ENG); ENVIRONMENT/ECOLOGY; ENVIRONMENTAL SCIENCES; Doğa ve Peyzaj Koruma; Çevre Bilimi (çeşitli); Su Bilimi; Fizik Bilimleri; Yaşam Bilimleri; Nature and Landscape Conservation; Environmental Science (miscellaneous); Aquatic Science; Physical Sciences; Life Sciences; non-fatal; occupational accidents; risk analyses; shipyards